2017
DOI: 10.3389/fonc.2017.00186
|View full text |Cite
|
Sign up to set email alerts
|

Quo natas, Danio?—Recent Progress in Modeling Cancer in Zebrafish

Abstract: Over the last decade, zebrafish has proven to be a powerful model in cancer research. Zebrafish form tumors that histologically and genetically resemble human cancers. The live imaging and cost-effective compound screening possible with zebrafish especially complement classic mouse cancer models. Here, we report recent progress in the field, including genetically engineered zebrafish cancer models, xenotransplantation of human cancer cells into zebrafish, promising approaches toward live investigation of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 141 publications
(142 reference statements)
0
54
0
Order By: Relevance
“…The zebrafish is an excellent model for in vivo investigation of disease mechanisms relevant to human disease including cancers and can also serve as a platform for the screening of therapeutic drugs [15] , [39] . Several previous studies in zebrafish cancer models in the brain [40] , liver [20] , [26] , [27] , [28] , and pancreas [41] have demonstrated that continued kras V12 expression is required for tumor maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…The zebrafish is an excellent model for in vivo investigation of disease mechanisms relevant to human disease including cancers and can also serve as a platform for the screening of therapeutic drugs [15] , [39] . Several previous studies in zebrafish cancer models in the brain [40] , liver [20] , [26] , [27] , [28] , and pancreas [41] have demonstrated that continued kras V12 expression is required for tumor maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…To date, an extensive list of improved zebrafish cancer models has been reported, including models to study neuroblastoma, brain cancer, eye cancer, leukemia, melanoma, uveal melanoma, and liver cancer, among others [ 177 ]. More complex models to study the mechanisms of tumor cell dissemination and metastases formation have also been reported [ 178 , 179 ].…”
Section: The Potential Of Zebrafish For Increasing the Translationmentioning
confidence: 99%
“…The zebrafish genome is sequenced, sharing 70% of homology with humans, namely in crucial pathways involved in vertebrate development and cancer. It is also reported that 82% of disease-causing human proteins have an ortholog in zebrafish [101].…”
Section: Zebrafish Xenograftsmentioning
confidence: 99%